2020
DOI: 10.21203/rs.3.rs-18686/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modified FOLFIRINOX as a second-line therapy following gemcitabine plus nab-paclitaxel therapy in metastatic pancreatic cancer

Abstract: Background There is no established second-line treatment after failure of gemcitabine plus nab-paclitaxel (GnP) therapy for metastatic pancreatic cancer (MPC). This study aimed to evaluate the efficacy and tolerability of the modified FOLFIRINOX (mFFX) as a second-line therapy for MPC and investigate prognostic factors for survival. Methods From 2015–2019, we retrospectively reviewed the medical records of patients receiving mFFX for MPC after failure of GnP therapy. Patients were treated every 2 weeks with mF… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In previous studies in the single-arm setting, the FOLFIRINOX regimen, including mFOLFIRINOX, showed favorable treatment outcomes as a second-line chemotherapy after the failure of GEM-based chemotherapy. 17,23,24,26,27 Response rates, PFS, and OS in patients with MPC were 10.6-22.2%, 2.8-5.4 months, and 7.0-9.8 months, respectively. 17,23,27 However, limited data exist regarding the direct comparison between FOLFIRINOX and fluoropyrimidine, including S-1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies in the single-arm setting, the FOLFIRINOX regimen, including mFOLFIRINOX, showed favorable treatment outcomes as a second-line chemotherapy after the failure of GEM-based chemotherapy. 17,23,24,26,27 Response rates, PFS, and OS in patients with MPC were 10.6-22.2%, 2.8-5.4 months, and 7.0-9.8 months, respectively. 17,23,27 However, limited data exist regarding the direct comparison between FOLFIRINOX and fluoropyrimidine, including S-1.…”
Section: Discussionmentioning
confidence: 99%
“…17,23,24,26,27 Response rates, PFS, and OS in patients with MPC were 10.6-22.2%, 2.8-5.4 months, and 7.0-9.8 months, respectively. 17,23,27 However, limited data exist regarding the direct comparison between FOLFIRINOX and fluoropyrimidine, including S-1. 28 In our current study of 78 patients with metastatic pancreatic adenocarcinoma after GnP failure, we observed significantly favorable response rates and PFS in the mFOLFIRINOX group compared with the S1 group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies investigated the efficacy of modified FOLFIRINOX in patients with GEM-refractory PDAC (19)(20)(21). Sawada et al reported the efficacy and good tolerability of modified FOLFIRINOX as second-line therapy after GnP (22). Although FOLFIRINOX poses a risk of serious adverse events, these studies have shown that it can be safely administered when doses are reduced.…”
Section: Discussionmentioning
confidence: 99%